Antimalarial activity of single-dose DSM265, a novel plasmodium dihydroorotate dehydrogenase inhibitor, in patients with uncomplicated Plasmodium falciparum or Plasmodium vivax malaria infection: a proof-of-concept, open-label, phase 2a study. Issue 8 (August 2018) - Llanos-Cuentas, Alejandro; Casapia, Martin; Chuquiyauri, Raúl; Hinojosa, Juan-Carlos; Kerr, Nicola; Rosario, Maria; Toovey, Stephen; Arch, Robert H; Phillips, Margaret A; Rozenberg, Felix D; Bath, Jade; Ng, Caroline L; et al.
Summary: Background: DSM265 is a novel, long-duration inhibitor of plasmodium dihydroorotate dehydrogenase (DHODH) with excellent selectivity over human DHODH and activity against blood and liver stages of Plasmodium falciparum . This study aimed to assess the efficacy of DSM265 in patients with P falciparum or Plasmodium vivax malaria infection. Methods: This proof-of-concept, open-label, phase 2a study was conducted at the Asociación Civil Selva Amazónica in Iquitos, Peru. Patients aged 18–70 years, weighing 45–90 kg, who had clinical malaria ( P falciparum or P vivax monoinfection) and fever within the previous 24 h were eligible. Exclusion criteria were clinical or laboratory signs of severe malaria, inability to take oral medicine, and use of other antimalarial treatment in the preceding 14 days. Patients were divided into cohorts of those with P falciparum (cohort a) or P vivax (cohort b) infection. Two initial cohorts received single oral doses of 400 mg DSM265. Patients were followed up for efficacy for 28 days and safety for 35 days. Further cohorts received escalated or de-escalated doses of DSM265, after safety and efficacy assessment of the initial dose. The primary endpoints were the proportion of patients achieving PCR-adjusted adequate clinical and parasitological response (ACPR) by day 14 for patients infected with P falciparum and the proportion of patients achieving a crude cure by day 14 for those infected with P vivax . Cohort success, the criteria for dose escalation, was defined as ACPR ( P falciparum ) or crude cure ( P vivax ) in at least 80% of patients in the cohort. The primary analysis was done in the intention-to-treat population (ITT) and the per-protocol population, and safety analyses were done in all patients who received the study drug. This study is registered at ClinicalTrials.gov (NCT02123290 ). Findings: Between Jan 12, 2015, and Dec 2, 2015, 45 Peruvian patients (24 with P falciparum [cohort a] and 21 with P vivax [cohort b] infection) were sequentially enrolled. For patients with P falciparum malaria in the per-protocol population, all 11 (100%) in the 400 mg group and eight (80%) of ten in the 250 mg group achieved ACPR on day 14. In the ITT analysis, 11 (85%) of 13 in the 400 mg group and eight (73%) of 11 in the 250 mg group achieved ACPR at day 14. For the patients with P vivax malaria, the primary endpoint was not met. In the per-protocol analysis, none of four patients who had 400 mg, three (50%) of six who had 600 mg, and one (25%) of four who had 800 mg DSM265 achieved crude cure at day 14. In the ITT analysis, none of five in the 400 mg group, three (33%) of nine in the 600 mg group, and one (14%) of seven in the 800 mg group achieved crude cure at day 14. During the 28-day extended observation of P falciparum patients, a resistance-associated mutation in the gene encoding the DSM265 target DHODH was observed in two of four recurring patients. DSM265 was well tolerated. The most common adverse events were pyrexia (20 [44%] of 45) and headache (18 [40%] of 45), which are both common symptoms of malaria, and no patients had any treatment-related serious adverse events or adverse events leading to study discontinuation. Interpretation: After a single dose of DSM265, P falciparum parasitaemia was rapidly cleared, whereas against P vivax, DSM265 showed less effective clearance kinetics. Its long duration of action provides the potential to prevent recurrence of P falciparum after treatment with a single dose, which should be further assessed in future combination studies. Funding: The Global Health Innovative Technology Fund, the Bill & Melinda Gates Foundation, the National Institutes of Health (R01 AI103058), the Wellcome Trust, and the UK Department of International Development.